SÍNTESE DE BIOÉTERES DA GLICERINA DO BIODIESEL DE BABAÇU UTILIZANDO LÍQUIDOS IÔNICOS COMO CATALISADORES E ENERGIA DE MICRO-ONDAS. - MENDONÇA, Sergiane de Jesus Rocha (2018)
Brazil is a great glycerin producer, a byproduct obtained in the process of biodiesel production. Due to it’s reduced added value, glycerin can be transformed in other commercial products, implying on the appreciation of the whole productive chain. The glycerin ethers synthesis in presence of acid catalysts and using biotechnological processes generates important industrial products, because they constitute potentiating additives in the combustion yield both in diesel and biodiesel. The present work addresses a study about the treatment and purification of babassu and soybean glycerin and it’s conversion in bio-ethers, using benzylic alcohol as an etherification agent and ionic liquids as catalysts in conventional heating and microwave assisted reactions. The babassu biodiesel glycerin was treated with phosphoric acid and purified with activated charcoal and commercial talc as adsorbents, characterized though physicochemical analyzes, FTIR, TG/DTG, DSC and CG-MS, obtaining glycerol with purity superior to 96%. The synthetized p-toluenosulfonate of pyridinium ionic liquid presented a good catalytic activity and was characterized by FTIR, ¹H NMR, ¹³C NMR and TG/DTG. The etherification reaction tests were realized using a complete experimental planning and a central composite design, aiming to find better reactive conditions with the objective of obtaining babassu glycerin bioethers. The investigated reactional parameters were temperature (90 - 180 °C), benzyl alcohol:glycerin molar ratio (1:1 - 4:1) and liquid ionic catalyst amount (5 - 15 wt%); The main products of the reactions were identified and quantified though the CG-EM and CG-DIC. The glycerin conversion in ethers, purified with charcoal and talc using conventional heating was of 72,81% and 89,78% respectively in 6h of reaction. The etherification of babassu glycerin biodiesel assisted by microwave favored the production of monoethers and diethers of glycerin with conversion of 87,40%, using the following reactional conditions determined by the surface response methodology experimental design with central composite design: 170 °C, ratio AB:G (4:1), 7,8% of LI [Py+][p-TSA-], 1200 W and 60 minutes of reaction. The obtained results demonstrate that the glycerin from babassu oil biodiesel generated an excellent effectiveness as regards of the production of bioethers, implying in a better financial exploitation in the industrial process as a whole.